Isolated thrombosis of cortical veins – Clinical and radiological correlation. (September 2021) - Murumkar, Vivek; Goyal, Sheetal; Priyadarshini Baishya, Priyanka; Peer, Sameer; Lanka, Vivek; Kulanthaivelu, Karthik; Saini, Jitender; Raghavendra, K.; Varun Reddy, Yerasi; Dattatraya Bhat, Maya
Highlights: ICVT constitutes a small fraction of cerebral venous thrombosis. Exaggerated sulcal blooming on SWI due to thrombosed vein represents SWI-cord sign. SWI-cord sign adjacent haemorrhagic infarction may suggest ICVT. Abstract: Isolated cortical venous thrombosis (ICVT) is a relatively rare clinical entity with non-specific clinical presentations. Anatomical variations in cortical veins and the lack of a gold standard imaging feature make the diagnosis of ICVT challenging. Headache and seizures were the most common presentations. The Vein of Trolard followed by superficial middle cerebral vein (SMCV) were the most commonly involved. Susceptibility Weighted Imaging (SWI) cord sign was observed in 100% of the cases. CT cord sign and filling defects on contrast enhanced CT were evident in 46.7% and 10% of the cases, respectively. Notably, in the absence of filling defect visualized on contrast CT, MRI, replacement of flow void was the surrogate marker for the ICVT. A high index of clinical suspicion, a thorough understanding of neurovascular anatomy, multiparametric, multiplanar MRI protocol is required to diagnose this rare entity. A serpiginous blooming structure within the subarachnoid space identifiable in less than two contiguous sections on SWI in the vicinity of haemorrhagic infarction should alert the clinician to the imaging possibility of ICVT.